Flu vaccination coverage among healthcare workers: the example of younger generations. (30th September 2020) - Di Pumpo, M; Lanza, T E; Villani, L; Aulino, G; Barbara, A; La Milia, D I; Moscato, U; Damiani, G; Ricciardi, W; Laurenti, P
Abstract: Flu vaccination is highly recommended among Healthcare Workers (HCWs). The low coverage in Italy among HCWs (mean 15.6% for 2016/17 flu season, ECDC) calls for new approaches. The aim of this study was to evaluate in which measure the vaccination coverage among HCWs registered during the 2019-2020 flu vaccination campaign in a large Teaching Hospital in Rome was affected by age and education. A retrospective observational quasi-experimental study was conducted. Descriptive and inferential statistical analysis (chi-square test, significance level of 0.05) were performed. The 2019-2020 flu vaccination campaign was aimed at more than 4000 employed HCWs (total coverage 24.2%). Vaccination was also extended to not-employed HCWs such as Medical Residents (MRs) and Medical Students (MSs) in clinical training. The coverage in this groups was higher (46.0% and 63.2% respectively) and the difference between them and the coverage among employed HCWs was statistically significant (p < 0.05); Further analysis was performed comparing MRs / MSs in clinical training with their respective professional group of employed HCWs, with a percentage of vaccinated Medical Doctors (MD) of 36.6%. MRs / MSs in clinical training coverage was higher than MDs coverage and the difference still proved to be statistically significant (p < 0.05). The higher coverage among MRs / MSs in clinical training could be explained, in general, in light of the more open-mindedness to prevention and to healthy lifestyles that characterizes young people with an up-to-date education. It could also be explained considering the specific culture and sense of responsibility of Medical Students and Medical Residents towards their high-demanding educational path and clinical training as an incentive not to get ill. Flu vaccination is highly recommended among HCWs. Younger generations, who represent the future of Healthcare, prove to be more open-minded and responsible towards good prevention practices such as this. Key messages: Flu vaccination is highly recommended among HCWs. Younger generations, who represent the future of Healthcare, prove to be more open-minded and responsible towards good prevention practices.